2021
DOI: 10.3390/ijms22179165
|View full text |Cite
|
Sign up to set email alerts
|

The Long Non-Coding RNA H19 Drives the Proliferation of Diffuse Intrinsic Pontine Glioma with H3K27 Mutation

Abstract: Diffuse intrinsic pontine glioma (DIPG) is an incurable paediatric malignancy. Identifying the molecular drivers of DIPG progression is of the utmost importance. Long non-coding RNAs (lncRNAs) represent a large family of disease- and tissue-specific transcripts, whose functions have not yet been elucidated in DIPG. Herein, we studied the oncogenic role of the development-associated H19 lncRNA in DIPG. Bioinformatic analyses of clinical datasets were used to measure the expression of H19 lncRNA in paediatric hi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…H3K27M mutations frequently occur in high-grade gliomas (HGG) in the midline of the brain, including those in the thalamus, brainstem and spinal cord in children and adolescents [ 61 ]. H3K27M mutation was found in 80% of children with diffuse intrinsic pontine glioma (DIPG) [ 62 ]. In recent years, it was found that H3K27ac increased in H3K27M HGG genome, and the enrichment of H3K27ac increased the expression of repeat elements in H3K27M HGG, which provided a theoretical basis for H3K27M HGG epigenetic therapy [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…H3K27M mutations frequently occur in high-grade gliomas (HGG) in the midline of the brain, including those in the thalamus, brainstem and spinal cord in children and adolescents [ 61 ]. H3K27M mutation was found in 80% of children with diffuse intrinsic pontine glioma (DIPG) [ 62 ]. In recent years, it was found that H3K27ac increased in H3K27M HGG genome, and the enrichment of H3K27ac increased the expression of repeat elements in H3K27M HGG, which provided a theoretical basis for H3K27M HGG epigenetic therapy [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Out of the 14 lncRNAs, eight of them were previously reported. H19 was reported to be upregulated in high-grade glioma and facilitated the proliferation of diffuse intrinsic pontine glioma ( Roig-Carles et al, 2021 ). LINC00346 promotes cell migration, proliferation, and apoptosis by targeting ROCK1( Chen et al, 2020 ) and miR-128-3p/SZRD1 axis ( Geng et al, 2020 ) in glioma.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging data are shining light on H19 lncRNA in glioma, which, similarly to LIN28A/B, works by suppressing let-7 to derepress let-7 targets. A recent study showed that in DIPG cells, H19 lncRNA expression is increased [ 61 ]. Meanwhile, let-7a-5 treatment decreases proliferation [ 61 ].…”
Section: Mechanisms Of Glioma Cell Suppression By Let-7mentioning
confidence: 99%
“…A recent study showed that in DIPG cells, H19 lncRNA expression is increased [ 61 ]. Meanwhile, let-7a-5 treatment decreases proliferation [ 61 ]. However, H19 decreases let-7a-5 levels via lncRNA:miR complementarity, which increases expression of let-7a-5 targets ( Figure 6 , [ 61 ]).…”
Section: Mechanisms Of Glioma Cell Suppression By Let-7mentioning
confidence: 99%
See 1 more Smart Citation